Role of E3 ubiquitin ligases and deubiquitinating enzymes in SARS-CoV-2 infection - Zhao, Mingjiu; Zhang, Mengdi; Yang, Zhou; Zhou, Zhiguang; Huang, Jiaqi; Zhao, Bin (Frontiers in Cellular and Infection Microbiology, 2023)
Ever since its emergence in 2019, COVID-19 has rapidly disseminated worldwide, engendering a pervasive pandemic that has profoundly impacted healthcare systems and the socio-economic milieu. A plethora of studies has been conducted targeting its pathogenic virus, SARS-CoV-2, to find ways to combat COVID-19. The ubiquitin-proteasome system (UPS) is widely recognized as a crucial mechanism that regulates human biological activities by maintaining protein homeostasis. Within the UPS, the ubiquitination and deubiquitination, two reversible modifications, of substrate proteins have been extensively studied and implicated in the pathogenesis of SARS-CoV-2. The regulation of E3 ubiquitin ligases and DUBs(Deubiquitinating enzymes), which are key enzymes involved in the two modification processes, determines the fate of substrate proteins. Proteins associated with the pathogenesis of SARS-CoV-2 may be retained, degraded, or even activated, thus affecting the ultimate outcome of the confrontation between SARS-CoV-2 and the host. In other words, the clash between SARS-CoV-2 and the host can be viewed as a battle for dominance over E3 ubiquitin ligases and DUBs, from the standpoint of ubiquitin modification regulation. This review primarily aims to clarify the mechanisms by which the virus utilizes host E3 ubiquitin ligases and DUBs, along with its own viral proteins that have similar enzyme activities, to facilitate invasion, replication, escape, and inflammation. We believe that gaining a better understanding of the role of E3 ubiquitin ligases and DUBs in COVID-19 can offer novel and valuable insights for developing antiviral therapies.